2016
DOI: 10.3390/ijms17111896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post-Translational Amidation on Islet Amyloid Polypeptide Conformational Ensemble: Implications for Its Aggregation Early Steps

Abstract: The human islet amyloid polypeptide (hIAPP) is an intrinsically disordered protein that can self-assemble into fibrillar aggregates that play a key role in the pathogenesis of the type II diabetes mellitus. hIAPP can transiently adopt sans-serifα-helix and sans-serifβ-strand conformations that could be important intermediate species on the fibrillization pathway. However, experimental studies of the monomeric peptide conformations are limited due to its high aggregation propensity, and the early steps of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
2
5
0
1
Order By: Relevance
“…A previous study predicted Rg values between 0.83 to 1.39 nm for the monomeric state of amylin, [32] and another study reported 0.918 nm for the gyration of hIAPP [33] . In addition, in an REMD simulation, an Rg between 0.88 to 0.97 nm was obtained [34] . Therefore, our results are in good agreement with this previous work.…”
Section: Resultssupporting
confidence: 92%
“…A previous study predicted Rg values between 0.83 to 1.39 nm for the monomeric state of amylin, [32] and another study reported 0.918 nm for the gyration of hIAPP [33] . In addition, in an REMD simulation, an Rg between 0.88 to 0.97 nm was obtained [34] . Therefore, our results are in good agreement with this previous work.…”
Section: Resultssupporting
confidence: 92%
“…[41] The sampling of helical conformation at the N-terminal residues in hIAPP monomer (Figure 6a) is consistent with that of Qiao et al, [51] which reported that residues 4-7 in the N-terminal region of hIAPP monomer displayed notable α-helical propensity in the conformational ensemble generated by extensive MD simulations. After 60 ns, the β-sheet conformation was mainly observed in N-terminal (region 2-4) and C-terminal residues (Ser34 and Asn35), which is consistent with the results reported by Tran et al [52] In the hIAPP-ANFLVH complex, the percentage population of the helix, turn, coil, and bend conformations were 41 � 3.37 %, 18 � 1.5 %, 30 � 2.52 %, and 9 � 0.79 %, respectively, and complete absence of β-sheet was observed ( Figure S4, Table 2). The absence of β-sheet structures in the conformational ensemble of the hIAPP-ANFLVH complex is consistent with circular dichroism (CD) results, which highlighted the prevention of the formation of β-sheet in hIAPP on the addition of ANFLVH peptide at equimolar or higher concentrations.…”
Section: Secondary Structure Analysis Of Hiapp and Hiapp-anflvh Complexsupporting
confidence: 92%
“…To determine whether PAM haploinsufficiency has an impact on islet amyloid formation and diabetes susceptibility, we crossed mice with beta cell expression of hIAPP with Pam +/− mice. IAPP is a PAM substrate and synthetic hIAPP variants with a free (nonamidated) COOH-terminus aggregate more slowly than COOH-terminally amidated forms [17,40]. We hypothesised that impaired amidation of hIAPP in Pam +/− mice may lead to production of hIAPP forms with altered fibril-forming kinetics, morphology and cytotoxicity [41].…”
Section: Discussionmentioning
confidence: 99%
“…Human, but not rodent, IAPP aggregates to form islet amyloid deposits in type 2 diabetes, likely contributing to islet inflammation and beta cell failure [14][15][16]. It is plausible that PAMmediated IAPP amidation could alter IAPP aggregation kinetics and, by extension, that PAM deficiency could influence IAPP-related islet pathology [17].…”
Section: Introductionmentioning
confidence: 99%